Voice Mismatches in English and Spanish Sluicing - Martín González, Javier (IBERIA: An International Journal of Theoretical Linguistics, 2011)
Voice mismatches are claimed to be disallowed in sluicing due to a morpho-syntactic requirement dictating that voice specifications must be isomorphic between the antecedent and the elliptical clause (Merchant 2007). However, following Vicente’s (2008) and Rodrigues et al.’s (2009) analysis of apparent P-stranding in Spanish sluicing, one must conclude that voice mismatches are a natural consequence of the need for copular constructions as sources for sluiced clauses in this language. The picture that emerges is one in which we need a mixed system of copular and non-copular sources in Spanish sluicing resolution. The paper also shows that only passive-active mismatches are possible and offers an explanation based on trivial structural requirements of subject DPs in copular clauses. Then, some interesting new data is analyzed with respect to English that suggest that we may also need the postulation of such a mixed system in this language, contrary to what is generally assumed. Furthermore, it is shown that voice mismatch data in English sluicing can be accounted for along the same lines as those used for Spanish. The cross-linguistic facts discussed throughout the paper also help to provide evidence for the proposal that, aside from semantic and pragmatic requirements, there are morpho-syntactic conditions to be considered in sluicing and also that sluicing involves the construction of full structures in the elided clauses that are later deleted at PF.